2014
DOI: 10.1002/star.201300289
|View full text |Cite
|
Sign up to set email alerts
|

Guarana powder polysaccharides: Characterization and rheological properties of starch

Abstract: Guarana seeds are described to contain starch as the main constituent. In this work, two fractions of starch were isolated from guarana seeds using dimethyl sulfoxide. The samples, named GD‐I and GD‐II were characterized and their rheological properties investigated. 13C NMR analysis confirmed the presence of starch in both fractions. GD‐I showed higher amylose content (51.4%) than GD‐II (33.0%). Elution profiles of GD‐I and GD‐II by high performance size exclusion chromatography indicated they were heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Previous studies have established a strong correlation between starch viscosity and amylopectin content. Amylopectin, with its intricate, reticulated structure and stronger intermolecular forces compared to amylose, plays a pivotal role in determining viscosity (Dalonso and de Oliveira Petkowicz, 2014). Notably, there were insignificant differences (p>0.05) in BD values among ER samples, indicating that their thermal stability is comparable.…”
Section: Rva Analysismentioning
confidence: 97%
“…Previous studies have established a strong correlation between starch viscosity and amylopectin content. Amylopectin, with its intricate, reticulated structure and stronger intermolecular forces compared to amylose, plays a pivotal role in determining viscosity (Dalonso and de Oliveira Petkowicz, 2014). Notably, there were insignificant differences (p>0.05) in BD values among ER samples, indicating that their thermal stability is comparable.…”
Section: Rva Analysismentioning
confidence: 97%
“…Besides the characterization of polyphenols and methylxanthines, several studies have investigated other aspects of guarana seed composition. Dalonso and Petkowicz (2014) characterized the polysaccharides of guarana seeds and showed that different starch fractions had distinct amylose and amylopectin content. Avato et al (2003) reported that guarana seed oil contained F I G U R E 2 Chemical structures of catechin and epicatechin, and simplified representation of proanthocyanidins type-A and type-B linkage 3% of cyanolipids and 28% of acylglycerols.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Besides the characterization of polyphenols and methylxanthines, several studies have investigated other aspects of guarana seed composition. Dalonso and Petkowicz (2014) characterized the polysaccharides of guarana seeds and showed that different starch fractions had distinct amylose and amylopectin content. Avato et al.…”
Section: Chemical Compositionmentioning
confidence: 99%